2022
DOI: 10.1155/2022/5798602
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Predictive Models with Visualized Machine Learning for Assessing the Risk of Lung Metastasis in Kidney Cancer Patients

Abstract: Objective. To establish and verify the clinical prediction model of lung metastasis in renal cancer patients. Method. Kidney cancer patients from January 1, 2010, to December 31, 2017, in the SEER database were enrolled in this study. In the first section, LASSO method was adopted to select variables. Independent influencing factors were identified after multivariate logistic regression analysis. In the second section, machine learning (ML) algorithms were implemented to establish models and 10-foldcross-valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…The disease’s early stages do not have any visible symptoms. As a result, people who want to receive medical treatment may already have kidney cancer that has spread to other parts of their bodies and may be experiencing related complications [ 1 ]. Malignant kidney tumors make up 2% of all cancer cases worldwide and are becoming more common.…”
Section: Introductionmentioning
confidence: 99%
“…The disease’s early stages do not have any visible symptoms. As a result, people who want to receive medical treatment may already have kidney cancer that has spread to other parts of their bodies and may be experiencing related complications [ 1 ]. Malignant kidney tumors make up 2% of all cancer cases worldwide and are becoming more common.…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested that parameters such as race, grade, T stage, N stage, surgery, tumor size, and distant metastasis in other sites were independent variables for LM. Similarly, Xu et al [ 29 ] developed machine learning-based models to evaluate the risk of developing lung metastasis in kidney cancer patients using the SEER database. They performed multivariate logistic regression and found that grade, T and N stage, tumor size, and metastasis to other sites, including the bone, brain, and liver, were all risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Цель исследования -анализ влияния прогностических факторов на показатели общей выживаемости у больных с метастазами рака почки в легкие. [12] костные метастазы, метастазы в печень и головной мозг были важными прогностическими предикторами метастазов в легких при раке почки, что подтверждается данными нашего исследования. В нашей работе только при однофакторном анализе выявлено влияние метастазов в кости, печень и лимфатические узлы на показатели ОВ у больных с ПКР (p<0,001).…”
Section: Introductionunclassified